NOTARY MEDIATING IN GEORGIA - Rosepashvili, Nana; Tkebuchava, Maka (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The alternative way of dispute solution or mediation is a method of dispute solution by negotiation, where neutral person-mediator helps opposing parties or their representatives to finish conflict arisen between them by mutually beneficial agreement. In this article we briefly review, notary mediation, course of notary mediation and legal content of made resolution, the question of resolution execution by writ of execution issued by notary, the terms of notary mediation and cost of notary mediation. Mediating is an alternative method of dispute solution in the way of negotiation, where neutral person-mediator helps opposed parties or their representatives to finish arisen conflict productively for both. The main point and purpose of mediating is to renew and preserve social relations between the parties. Іn this article we briefly review, notary mediation, course of notary mediation and legal content of made resolution, the question of resolution execution by writ of execution issued by notary, the terms of notary mediation and cost of notary mediation. International legislation, also as Georgian, did not make a strict regulation of procedural questions, entrusted their determination to parties and mediator. In this case, we do not review all possible approach and stage, but cite only these stages, that may be used the most effectively in notary practice: Pre mediating is the first stage; this is the time for preparation and agreement about carrying out of notary mediating procedure. Before starting process, mediating parties and mediator study case history and obtain information about mediating process. Before starting of notary mediating process, it is necessary to determine a place, where this process must be carried out. Proceeding of mediating procedures is the second stage. Notary mediating is started by forming of requests and positions of party/parties regarding justiciable questions that determine agenda of mediating process. Mediating Institute has as positive so negative sides. The positive side is: cheapness, rapidity, preserving of relationship between the parties, confidentiality, reaching a consensus and comprehension of objective opinion about the main point of litigation by both party. And negative side is that the second party may not agree to participate in the mediating, case resolve is not guaranteed. Notary act is not always a result of mediating process, as despite participation of notary, the parties may not agree and notary act not to be executed, for instance, not to reach consensus over essentials (subject, price and etc.) though, mediating must be related to notary act execution needed for the parties, that is envisaged by law or agreement. Legal consultations and negotiations over the questions, that are not related to notary act is prerogative of advocates and honest lawyers and not of person authorized by state. By this brief review we may conclude, that notary mediating, as an alternative method of dispute solution is new in Georgian law. It is indisputable, that it is necessary conciliator technologies to be developed, that is confirmed by practice of foreign countries, scientists’ interest towards research of mediating technologies and transformation and support of state towards this field. As a result we get to save time and funds, less conflict and what is important harmonization of people relationships that is a necessary condition of successful development of society and joining European fellowship of country.